A Clinical Trial of Intravenous Peramivir Compared with Oral Oseltamivir for the Treatment of Seasonal Influenza in Hospitalized Adults. Issue 5 (July 2013) - Ison, Michael G; Hui, David S; Clezy, Kate; O'Neil, Brian J; Flynt, Amy; Collis, Philip J; Simon, Thomas J; Alexander, W James
Background: Seasonal interpandemic influenza causes >200, 000 annual hospitalizations in the United States. Optimal antiviral treatment in hospitalized patients is not established. Methods: During three interpandemic influenza seasons, 137 patients hospitalized with suspected acute influenza were randomized to 5-day treatment with intravenous peramivir 400 mg or 200 mg once daily or oral oseltamivir 75 mg twice daily. Time to clinical stability and quantitative changes in viral titres from nasopharyngeal specimens were primary and key secondary end points, respectively. Results: Infection was confirmed in 122 patients with influenza A (H1N1), influenza A (H3N2) or influenza B. Median times (95% CI) to clinical stability were 37.0 h (22.0, 48.7) with peramivir 400 mg, 23.7 h (16.0, 38.9) with peramivir 200 mg and 28.1 h (22.0, 37.0) with oseltamivir ( P =0.306). Patients ( n =97) who were clinically unstable at enrolment had median times (95% CI) to clinical stability of 24.3 h (21.2, 47.5) with peramivir 400 mg, 31.0 h (17.2, 47.7) with peramivir 200 mg and 35.5 h (23.3, 37.9) with oseltamivir ( P =0.541). Titres of influenza A viruses in nasopharyngeal specimens decreased similarly across treatments, but more rapid decreases in titres of influenza B occurred with peramivir treatment. There were no deaths among patients with confirmed influenza and the incidence of adverse events was low and generally similar among treatment groups. Conclusions: Treatment of acute seasonal influenza in hospitalized adults with either peramivir or oseltamivir resulted in generally similar clinical outcomes. Treatment with peramivir was generally safe and well tolerated and could be of benefit in this population.